1987
DOI: 10.1073/pnas.84.9.2808
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of a cDNA clone encoding the liver cell adhesion molecule, L-CAM.

Abstract: The liver cell adhesion molecule (L-CAM) appears on non-neural epithelial tissues and mediates calciumdependent adhesion in these tissues both in the embryo and in the adult. It appears on cell surfaces as a glycoprotein of Mr 124,000 but is synthesized as a precursor of Mr 135,000. We have isolated and determined the nucleic acid sequence of a cDNA clone (XL320) encoding chicken L-CAM. The 5' end of this clone has an open reading frame extending for 2520 base pairs, followed by an 850-base-pair untranslated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(88 citation statements)
references
References 33 publications
(45 reference statements)
3
84
0
1
Order By: Relevance
“…Some of the properties of these cadherins are similar in a number of respects, such as the molecular weight, the Ca2+ requirement for their activity, and Ca2+ protection against protease (Shirayoshi et al, 1986). Amino acid sequences deduced from cDNA cloning have clearly shown that cadherins belong to a protein family (Gallin et al, 1987;Nagafuchi et al, 1987;Nose et al, 1987;Ringwald et al, 1987;Hatta et al, 1988;Miyatani et al, 1989;Shimoyama et al, 1989). The cadherin molecule is divided by a transmembrane domain into a large extracellular domain at the N-terminal side and a small cytoplasmic domain at the C-terminal side.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the properties of these cadherins are similar in a number of respects, such as the molecular weight, the Ca2+ requirement for their activity, and Ca2+ protection against protease (Shirayoshi et al, 1986). Amino acid sequences deduced from cDNA cloning have clearly shown that cadherins belong to a protein family (Gallin et al, 1987;Nagafuchi et al, 1987;Nose et al, 1987;Ringwald et al, 1987;Hatta et al, 1988;Miyatani et al, 1989;Shimoyama et al, 1989). The cadherin molecule is divided by a transmembrane domain into a large extracellular domain at the N-terminal side and a small cytoplasmic domain at the C-terminal side.…”
Section: Introductionmentioning
confidence: 99%
“…An XhoI/BamHI fragment containing the majority of the Ecadherin coding region was isolated from plasmid pEC320 (40). pBK-CMV expression vector (Stratagene) was modified by digestion with EcoRI and KpnI followed by polishing with mung bean nuclease and ligation to remove part of the polylinker.…”
Section: Construction Of E-cadherin Expressionmentioning
confidence: 99%
“…Such a molecular weight discrepancy is commonly found for transmembrane glycoproteins (e.g., L-CAM, Gallin et al, 1987). Consistent with the known transmembrane nature of dg2/3 ) hydropathy plots (Hopp and Woods, 1981) identified a single region of 35 amino acids showing characteristics of a transmembrane sequence (Fig.…”
Section: Sequencing Of Cdna Clonesmentioning
confidence: 52%
“…The extracellular domains of Percentage identity between extrac¢lhilar domain sequences can be found by refering to the figure at the intersection of rows and columns corresponding to any pair of sequences. Bovine N-cadherin, Liaw et al (1990); chick N-cadherin, Hatta et al (1988); mouse P-cadherin, Nose et al (1987); mouse E-cadherin, Nagafuchi et al (1987); chick L-CAM, Gallin et al (1987); bovine dgl, Koch et al (1990). (Fig.…”
Section: Sequence Homologies With Cadherins and Dglmentioning
confidence: 99%
See 1 more Smart Citation